Analysis of EU investment on rural development and its impact on Portuguese rural regions in the period 2011-2021 - Isabel Abreu; Joaquim Mourato; Francisco J. Mesías (Economía Agraria y Recursos Naturales)
EU's rural areas are an essential part of the European way of life, covering more than 75 % of the Union's territory and housing over 25 % of its population. However, they experience major imbalances compared to urban areas. Thus, it is important to analyse whether EU's rural development (RD) policy is effective in promoting the development of rural areas. This study uses a RD index for 9 Portuguese NUTS 3 regions, with data from 2011 and 2021. The results are then compared with the financial support delivered by EU funds and show their impact on RD in Portugal.